Evaluation of RNase therapy in systemic lupus erythematosus: a randomised phase 2a clinical trial of RSLV-132 - Susan A Boackle; Daniel J Burge; James Posada (Lupus Science and Medicine)
Background Circulating, extracellular RNA is the primary trigger of type I interferon in systemic lupus erythematosus (SLE), and interferon is known to play a central pathogenic role in the disease. RSLV-132 is a catalytically active human RNase molecule fused to human IgG1 Fc designed to digest RNA and thereby decrease the chronic inflammation associated with SLE. The drug was evaluated in a cohort of patients with SLE with moderate-severe cutaneous disease activity and the presence of RNA immune complexes. The primary objective of the study was the assessment of the impact of 13 doses of 10 mg/kg RSLV-132 over 6 months on the mean Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) score.Methods Sixty-five patients meeting the entry criteria of a baseline CLASI score of 10 or greater and positivity of at least one of five autoantibodies to RNA-binding proteins (SM/RNP, SSA/Ro, SSB/La, Sm, RNP) were randomly assigned (2:1) to receive 13 doses of RSLV-132 10 mg/kg or placebo, respectively. Participants received study drug for 24 weeks on days 1, 8, 15, 29, 43, 57, 71, 85, 99, 113, 127, 141 and 155 with an end-of-treatment visit on day 169 and a follow-up visit at the end of the study on day 215. The primary objective was assessed on days 85 and 169. Secondary objectives included assessment of systemic disease activity using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), the British Isles Lupus Assessment Group 2004 Index and the Physician’s Global Assessment. Data from these instruments were used to calculate the SLE Responder Index 4 (SRI-4) and the British Isles Lupus Assessment Group-based Composite Lupus Assessment (BICLA) scores.Results The mean CLASI score change from baseline at day 169 was −5.7 (±7.0) in the placebo group and −6.2 (±8.5) in the RSLV-132 group. A subgroup of participants with moderate-severe systemic disease activity and high baseline SLEDAI scores (≥9) were analysed with respect to BICLA and SRI-4 responses. The RSLV-132 treated participants in the high SLEDAI subgroup had a greater percentage of BICLA responses (62% vs 44%) and SRI-4 responses (23% vs 11%) as compared with placebo. A second subgroup of participants with high baseline CLASI scores (≥21) were analysed with respect to BICLA and SRI-4 responses. The RSLV-132 treated participants in the high CLASI subgroup had a greater percentage of BICLA responses (28% vs 8%) and SRI-4 responses (39% vs 8%) as compared with placebo.Conclusions Six months of RSLV-132 therapy consisting of a weekly loading dose of RSLV-132 for 1 month, followed by 5 months of biweekly administrations did not significantly improve the mean CLASI score relative to placebo in this cohort of patients with SLE. The study entry criteria selected patients with moderate-severe cutaneous disease activity and no minimum SLEDAI score, which resulted in a wide range of systemic disease activity from inactive to severe as measured by SLEDAI. When the participants with higher SLEDAI and CLASI scores were analysed, a trend towards clinical improvement favouring RSLV-132 was observed. The results warrant further evaluation of RSLV-132 in SLE and suggest that patients with more active systemic disease are most likely to benefit from RNase therapy.